Genomics of Parallel Ecological Speciation in Lake Victoria Cichlids. (2nd April 2018) - Meier, Joana Isabel; Marques, David Alexander; Wagner, Catherine Elise; Excoffier, Laurent; Seehausen, Ole
Abstract: The genetic basis of parallel evolution of similar species is of great interest in evolutionary biology. In the adaptive radiation of Lake Victoria cichlid fishes, sister species with either blue or red-back male nuptial coloration have evolved repeatedly, often associated with shallower and deeper water, respectively. One such case is blue and red-backed Pundamilia species, for which we recently showed that a young species pair may have evolved through "hybrid parallel speciation". Coalescent simulations suggested that the older species P. pundamilia (blue) and P. nyererei (red-back) admixed in the Mwanza Gulf and that new "nyererei-like" and "pundamilia-like" species evolved from the admixed population. Here, we use genome scans to study the genomic architecture of differentiation, and assess the influence of hybridization on the evolution of the younger species pair. For each of the two species pairs, we find over 300 genomic regions, widespread across the genome, which are highly differentiated. A subset of the most strongly differentiated regions of the older pair are also differentiated in the younger pair. These shared differentiated regions often show parallel allele frequency differences, consistent with the hypothesis that admixture-derived alleles were targeted by divergent selection in the hybrid population. However, two-thirds of the genomic regions that are highly differentiated between the younger species are not highly differentiated between the older species, suggesting independent evolutionary responses to selection pressures. Our analyses reveal how divergent selection on admixture-derived genetic variation can facilitate new speciation events.